The derivation and visualization of supply network risk profiles from product architectures. Issue 5 (26th May 2022) - McKay, Alison; Chittenden, Richard; Hazlehurst, Thomas; de Pennington, Alan; Baker, Richard; Waller, Tony
Abstract: The architectures of extended enterprises, including the supply networks that design, develop and support large, complex, engineered products, often reflect system‐level design decisions made very early in the product development process. Design tools used at this, preliminary design, stage focus on the physics and optimization of product system behaviors. Comparable tools for the consideration of extended enterprise perspectives at this stage are not available despite the costs of non‐quality often attributed to supply chain issues related to early design decisions. This paper introduces an interface to a discrete event simulation package that derives supply chain processes from product system architectures, so enabling the quantification and visualization of supply chain risk in early design decisions. The interface uses input data, in the form of a product architecture and associated make‐buy scenarios, which are available in the preliminary design process. Supplier data needed to drive the simulations is predefined and editable by users. Results from a proof‐of‐concept software prototype demonstrate the feasibility of generating enterprise architectures from product architectures and coupling these with a systems design vee model to create executable simulation models that can be used to identify, quantify and visualize engineering supply chain process operations and consequential risks.